Comparison of gastrointestinal landmarks using the gas‐sensing capsule and wireless motility capsule. Issue 9 (9th September 2022) - Thwaites, Phoebe A.; Yao, Chu K.; Maggo, Jasjot; John, James; Chrimes, Adam F.; Burgell, Rebecca E.; Muir, Jane G.; Parker, Francis C.; So, Daniel; Kalantar‐Zadeh, Kourosh; Gearry, Richard B.; Berean, Kyle J.; et al.
Summary: Background: Accurate definition of the gastroduodenal and ileocaecal junctions (GDJ, ICJ) is essential for the measurement of regional transit times. Aims: To compare the assessment of these landmarks using the novel gas‐sensing capsule and validated wireless motility capsule (WMC), and to evaluate intra‐subject variance in transit times Methods: Healthy subjects ingested the gas‐sensing capsule and WMC tandemly in random order. Inter‐observer agreement was evaluated by intra‐class correlation coefficient (ICC). Agreement between the paired devices' transit times was assessed using Bland–Altman analysis; coefficient of variation was performed to express intra‐individual variance in transit times. Similar analyses were completed with tandemly ingested gas‐sensing capsules. Results: The inter‐observer agreement for landmarks for both capsules was excellent (mean ICC ≥0.97) in 50 studies. The GDJ was identifiable in 92% of the gas‐sensing capsule studies versus 82% of the WMC studies ( p  = 0.27); the ICJ in 96% versus 84%, respectively ( p  = 0.11). In the primary cohort ( n  = 26), median regional transit times differed by less than 6 min between paired capsules. Bland–Altman revealed a bias of −0.12 (95% limits of agreement, −0.94 to 0.70) hours for GDJ and − 0.446 (−2.86 to 2.0) hours for ICJ. Similar results were found in a demographically distinct validation cohort ( n  = 24). For tandemly ingested gas‐sensing capsules, coefficients of variation of transit times were 11%–35%, which were similar to variance between the paired gas‐sensing capsule and WMC, as were the biases. The capsules were well tolerated. Conclusions: Key anatomical landmarks are accurately identified with the gas‐sensing capsule in healthy individuals. Intra‐individual differences in transit times between capsules are probably due to physiological factors. Studies in populations with gastrointestinal diseases are now required. Abstract : Anatomical landmarks used to determine regional transit times are accurately identified by the novel gas‐sensing capsule when compared with the wireless motility capsule.